THE EFFECT OF E-COMMERCE AND THE USE OF MANAGEMENT INFORMATION SYSTEMS ON FINANCIAL PERFORMANCE - Sridarta, Yenni Maria; Subagya, Yusup Hari (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2024)
After Covid-19, MSME players are trying to utilize technology to develop their businesses to revive themselves and strengthen their market share so they can compete. MSME players try to take advantage of technology through the use of E-commerce and the use of Management Information Systems. The aim of this research is to determine the partial or simultaneous influence of the use of E-commerce and the use of Management Information Systems on the financial performance of Post-Covid-19 Batik MSMEs in Laweyan Surakarta. The method used is quantitative research by distributing questionnaires based on a Likert scale. The research results show that both partially and simultaneously, the use of E-commerce and Management Information Systems has a significant positive effect on the financial performance of Batik MSMEs in Laweyan Surakarta.